Self-assembled arrays of polyoxometalate-based metal–organic nanotubes for proton conduction and magnetism. Issue 56 (18th June 2015) - Jiao, Yan-Qing; Zang, Hong-Ying; Wang, Xin-Long; Zhou, En-Long; Song, Bai-Qiao; Wang, Chun-Gang; Shao, Kui-Zhan; Su, Zhong-Min
Abstract : The first polyoxometalate-based metal–orangic nanotube via covalent bonds has been synthesized, in which POMs act as linkers holding together the metal–organic nanotubes to construct 3D nanotubular arrays. Abstract : The first polyoxometalate-based metal–organic nanotube constructed via covalent bonds has been synthesized. POM anions stick the metal–organic nanotubes to build 3D nanotubular arrays. The stability, magnetic and proton conducting properties are investigated.